2011
DOI: 10.1038/jcbfm.2011.164
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypoxemia during Initial Reperfusion Alleviates the Severity of Secondary Energy Failure and Protects Brain in Neonatal Mice with Hypoxic-Ischemic Injury

Abstract: Reperfusion triggers an oxidative stress. We hypothesized that mild hypoxemia in reperfusion attenuates oxidative brain injury following hypoxia-ischemia (HI). In neonatal HI-mice, the reperfusion was initiated by reoxygenation with room air (RA) followed by the exposure to 100%, 21%, 18%, 15% oxygen for 60 minutes. Systemic oxygen saturation (SaO(2)), cerebral blood flow (CBF), brain mitochondrial respiration and permeability transition pore (mPTP) opening, markers of oxidative injury, and cerebral infarcts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
2
14
0
1
Order By: Relevance
“…To our knowledge, it is the first study to examine the effect of hyperoxia after HI on long-term injury development in gray and white matter in a neonatal rat model using manganeseenhanced MRI in combination with DTI and anatomical imaging. Although some experimental studies have found no effect (10) or that hyperoxia limits injury (11), mounting experimental data indicate that hyperoxia exacerbates injury after HI in the immature brain (5,12). Our study corroborates these findings and adds important knowledge to the effect of hyperoxia on the prolonged evolution of injury in gray and white matter.…”
Section: Strengths and Limitationssupporting
confidence: 81%
“…To our knowledge, it is the first study to examine the effect of hyperoxia after HI on long-term injury development in gray and white matter in a neonatal rat model using manganeseenhanced MRI in combination with DTI and anatomical imaging. Although some experimental studies have found no effect (10) or that hyperoxia limits injury (11), mounting experimental data indicate that hyperoxia exacerbates injury after HI in the immature brain (5,12). Our study corroborates these findings and adds important knowledge to the effect of hyperoxia on the prolonged evolution of injury in gray and white matter.…”
Section: Strengths and Limitationssupporting
confidence: 81%
“…Here we found that the MAP and CBF decreased to a greater degree in the ligated hemisphere rats treated with severe hypoxia (PaO 2 < 50 mmHg) than in those treated with mild to moderate hypoxia (PaO 2 > 50 mmHg), suggesting that hypoxemia applied after unilateral CCA ligation reduced the systemic blood pressure and hypotension along with hypoxemia likely contributed to a greater decline in CBF. This may be due to impaired autoregulation and reduced cerebrovascular reserve under severe hypoxia[31, 32]. In the present study, we found that hypercapnia treatment resulted in CBF recovery in rats treated with mild to moderate hypoxia (PaO 2 > 50 mmHg) but not in rats treated with severe hypoxia (PaO 2 < 50 mmHg) accompanied by a MAP decrease.…”
Section: Discussionsupporting
confidence: 39%
“…Alternatively, it may reflect a greater loss of cerebrovascular auto-regulation in more severe cases (25). In experimental models of hypoxic-ischemic injury, a decrease in cerebral oxygenation and/or cerebral perfusion alleviates the extent of reperfusion-driven cerebral injury, suggesting that the relative increase in cerebral blood flow during TH is maladaptive (26,27). In clinical trials in newborns with HIE, TH resulted in only partial improvements in death and neurological outcomes (15,28,29).…”
Section: Discussionmentioning
confidence: 99%